OFFRP: optimised fruit fly based routing protocol with congestion control for UAVs guided ad hoc networks. (2018) - Sharma, Vishal; You, Ilsun; Kumar, Rajesh; Chauhan, Varun
Unmanned aerial vehicles (UAVs) have gained a lot of attention from the researchers across the globe. Their autonomous capabilities provide vast range of applications such as disaster management, surveillance, border security and inter-civilian activities. UAV networks have a major issue regarding the data flow and routing. UAVs operate in different band as compared to the ground nodes. Hence, there is a chance of congestion that may fail the whole network. Prediction of such congestion states can provide continuous connectivity. For this, a new optimised fruit fly routing protocol (OFFRP) is proposed which uses the properties of existing fruit fly optimisation algorithm for finding appropriate routes. The search of food sources by fruit flies using their smell index forms the basis of the proposed protocol. The proposed protocol is evaluated using standard network simulations and is compared with all the major routing protocols as well as existing TCP-oriented congestion control algorithms.